Response of soil organic carbon and its fractions to natural vegetation restoration in a tropical karst area, southwest China - Zhang, Bei; Xu, Chaohao; Zhang, Zhonghua; Hu, Cong; He, Yeyong; Huang, Kuaikuai; Pang, Qingling; Hu, Gang (Frontiers in Forests and Global Change, 2023)
The dynamics of soil organic carbon (SOC) and its fractions are important for evaluating the vegetation restoration effect and carbon cycle of the ecosystem. Here, SOC fractions, including light fraction organic carbon (LFOC), heavy fraction organic carbon (HFOC), and labile organic carbon (LOC) fractions (including water-soluble organic carbon, WSOC, readily oxidizable organic carbon, ROC, particulate organic carbon, POC, and microbial biomass carbon, MBC), were investigated at four soil depths under five restoration stages in a tropical karst area in southwest China. This study showed that the content of SOC and its fractions significantly increased with vegetation restoration and decreased with increasing soil depth at each restoration stage (p < 0.05). Additionally, LFOC was more sensitive to vegetation restoration, whereas HFOC was the main storage form of SOC. The LOC fractions in the surface soil layer were significantly higher than those in the lower, and the percentages of some LOC fractions (POC/SOC and MBC/SOC) significantly decreased with increasing soil depth, indicating that SOC was more stable in the lower layer than in the surface layer. Correlation analysis showed that SOC was significantly and positively correlated with its fractions. Moreover, SOC and its fraction were positively correlated with soil chemical factors (TN, TP, AP, AK, ECa, EMg, NH4+-N, and NO3–-N) and negatively correlated with bulk density (BD) at a significant level (p < 0.05). Moreover, redundancy analysis showed that the 12 soil physicochemical factors explained 70.99% of the variation in SOC and its fractions, with AK, NH4+-N, and BD being the main factors, explaining 19.38, 17.24, and 10.52% of the variation, respectively. The structural equation mode analysis showed that soil properties, above-ground biomass, and litterfall explained most of the variation in SOC (59%), LFOC (79%), HFOC (81%), and LOC (61%). Soil properties and above-ground biomass significantly affected SOC, LFOC, and HFOC content mainly through indirect effects, while the total phosphorus content of the litterfall could directly and significantly affect SOC, LFOC, and HFOC content. NH4+-N and AK of soil factors had direct effects on LFOC and LOC accumulation, respectively. This study provides a valuable perspective for estimating carbon sink potential and constructing carbon sink models in karst areas.